Occupational contact dermatitis in hairdressers: an analysis of patch test data from the Danish Contact Dermatitis Group, 2002–2011. (26th December 2013) - Schwensen, Jakob F.; Johansen, Jeanne D.; Veien, Niels K.; Funding, Anne T.; Avnstorp, Christian; Østerballe, Morten; Andersen, Klaus E.; Paulsen, Evy; Mortz, Charlotte G.; Sommerlund, Mette; Danielsen, Anne; Andersen, Bo L.; et al.
Summary Background Occupational contact dermatitis among hairdressers is frequent, owing to daily exposure to irritants and allergens. Objectives To identify sensitization to the most common allergens associated with the occupation of hairdressing. Methods Patch test results of 399 hairdressers and 1995 matched controls with contact dermatitis, registered by the Danish Contact Dermatitis Group between January 2002 and December 2011, were analysed. All patients were patch tested with the European baseline series, and hairdressers were additionally tested with the hairdressing series. Results Occupational contact dermatitis (p < 0.001) and hand eczema (p < 0.001) were observed significantly more often among hairdressers than among controls. Atopic dermatitis was less commonly observed among hairdressers (21.3%) than among controls (29.4%) (p < 0.01). Allergens from the European baseline series with a statistically significant association with the occupation of hairdressing were p‐phenylenediamine, thiuram mix, and benzocaine. Frequent sensitizers from the hairdressing series were ammonium persulfate, toluene‐2, 5‐diamine, 3‐aminophenol, and 4‐aminophenol. Cysteamine hydrochloride and chloroacetamide emerged as new sensitizers. Conclusions These results indicate a healthy worker effect among hairdressers diagnosed with eczema. Ammonium persulfate and p‐phenylenediamine remain frequent sensitizers in hairdressers with contact dermatitis. Cysteamine hydrochloride and chloroacetamide should be included in future surveillance studies.